2023
DOI: 10.1073/pnas.2304841120
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli small heat shock protein IbpA plays a role in regulating the heat shock response by controlling the translation of σ 32

Abstract: Small heat shock proteins (sHsps) act as ATP-independent chaperones that prevent irreversible aggregate formation by sequestering denatured proteins. IbpA, an Escherichia coli sHsp, functions not only as a chaperone but also as a suppressor of its own expression through posttranscriptional regulation, contributing to negative feedback regulation. IbpA also regulates the expression of its paralog, IbpB, in a similar manner, but the extent to which IbpA regulates other protein expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The nonconventional function of IbpA Ec as an aggregation-sensor tightly suppresses IbpA Ec expression under aggregation-free conditions but enables cells to rapidly upregulate the IbpA Ec levels upon acute aggregation stress, such as heat shock ( 10 , 18 ). Moreover, a recent study has demonstrated that IbpA Ec also downregulates the expression of other Hsps by inhibiting the translation level of the heat shock transcription factor σ 32 , which highlights the general importance of IbpA in the heat shock response regulation ( 19 ).…”
mentioning
confidence: 98%
“…The nonconventional function of IbpA Ec as an aggregation-sensor tightly suppresses IbpA Ec expression under aggregation-free conditions but enables cells to rapidly upregulate the IbpA Ec levels upon acute aggregation stress, such as heat shock ( 10 , 18 ). Moreover, a recent study has demonstrated that IbpA Ec also downregulates the expression of other Hsps by inhibiting the translation level of the heat shock transcription factor σ 32 , which highlights the general importance of IbpA in the heat shock response regulation ( 19 ).…”
mentioning
confidence: 98%